2019
DOI: 10.1186/s12871-019-0719-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness-analysis of ultrasound guidance for central venous catheterization compared with landmark method: a decision-analytic model

Abstract: Background Ultrasound guidance for central venous catheterization is a commonly used alternative to the conventional landmark method. Because from the German perspective, the cost-effectiveness of ultrasound guidance is unclear, this study examined the cost-effectiveness of ultrasound guidance versus the landmark method for adults undergoing a central venous catheterization. Methods A decision-tree based model was built to estimate the costs of averted catheter-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The femoral venous puncture guided by anatomical landmarks was amply compared to the femoral venous puncture guided by ultrasonography. The latter showed evidence of a significant increase in success rate of the procedure 13,14 and reduced the number of attempts and the number of complications related to the puncture. 13 Additionally, the average cost of the ultrasonography-guided procedure was lower than that of guided by anatomical landmarks.…”
Section: Case Reportmentioning
confidence: 88%
See 1 more Smart Citation
“…The femoral venous puncture guided by anatomical landmarks was amply compared to the femoral venous puncture guided by ultrasonography. The latter showed evidence of a significant increase in success rate of the procedure 13,14 and reduced the number of attempts and the number of complications related to the puncture. 13 Additionally, the average cost of the ultrasonography-guided procedure was lower than that of guided by anatomical landmarks.…”
Section: Case Reportmentioning
confidence: 88%
“…13 Additionally, the average cost of the ultrasonography-guided procedure was lower than that of guided by anatomical landmarks. 14 Both experienced operators and residents showed better results with the ultrasonography-guided method, although skilled operators experienced a more modest benefit when compared to physicians under training. 15 Puncture of the femoral vein guided by ultrasonography diminishes the cost and the chance of complications, while it increases the safety and success rate of the procedure.…”
Section: Case Reportmentioning
confidence: 94%
“…The use of ultrasound in vascular puncture and catheterization is the most basic application. Many studies have reported that ultrasound-guided central venous catheterization can improve the success rate of puncture, reduce the length of puncture duration and reduce the incidence of complications related to puncture and catheterization [ 8 , 9 ]. However, puncture and catheterization with ultrasound guidance does not mean that the approach can be selected casually.…”
Section: Discussionmentioning
confidence: 99%
“…Concerningly, although it is well reported that ultrasound use in CVAD insertion not only decreases complications 18 but is also cost‐effective, 18 only a minority of intensivists recommended ultrasound training, and that a fraction of the ICU fellows do not use ultrasound regularly. A six‐step systematic approach for ultrasound‐guided CVAD insertion has been recommended, which includes sequential steps from identifying location and patency of vein to real‐time ultrasound‐guided puncture and confirming needle, wire and catheter 16 .…”
Section: Discussionmentioning
confidence: 99%